Synthesis of Novel Guanidine-Schiff-Base Iron(III) and Zinc(II) Complexes - Conrads, Christian; Eilers, Maverick; Hülsken, Noah; Langletz, Tim; Hoffmann, Alexander; Herres-Pawlis, Sonja (Synthesis, 2025)
Hybrid guanidine ligands and their metal complexes are an important field of research due to their diverse applications and highly modular structure. In this work, the synthesis of four bench-stable iron(III) and zinc(II) complexes of two novel tridentate guanidine-Schiff-base ligands is presented. Although the ligands themselves were found to be unstable, the preparation of the stable metal complexes could be conducted on a gram scale and in high yields (≥88%) without isolation of the corresponding unstable ligand. All complexes were characterized by single-crystal X-ray diffraction, and their structural features are discussed.
Keywords: Guanidine; Iron; Zinc; Schiff base; Imine; Tridentate ligands; Pincer